Characterizing Passively Q-switched Fiber Laser in LiDAR Application - Mafroos, Mahroof Mohamed; Ameelia, Nur; Jameela, Husni Hani; Hamzah, Azura (International Journal of Integrated Engineering, 2023)
A LiDAR system consists of a Q-switched fiber laser that emits light pulses to measure the distance from the target. We have experimentally demonstrated a passively Q-switched erbium-doped fiber laser (EDFL) by employing graphene saturable absorber (SA). The SA was prepared by dipping a polyvinyl alcohol (PVA) thin film into the graphene solution. Once the SA was fabricated, it can be placed in the cavity to perform pulses and it is operating at 1558.92 nm. The shortest pulse received is 3.9 µs and generated at the repetition rate of 115 kHz. The pulses are stable between pump powers of 59.6mW and 127.1 mW. At the maximum pump power value of 127.1 mW, The laser cavity produced pulses with a 1.4mW output power and a 1.1nJ pulse energy.